(untitled) (Italian Review of Legal History, 2021)
The Nice-born jurist Giovanni de Foresta is a little-known and little-studied figure, despite his considerable contribution to the cause of the unity of Italy. A supporter of Cavour, he sat in the Subalpine Chamber for two legislatures, the IV and the V, and held two important government’s positions: he was Minister of Grace and Justice in the first D’Azeglio government and in the second Cavour government, around the time in that the laws “Siccardi” were in force. My paper aims to explain how De Foresta tried to develop his draft bills of renewal of justice and the judicial system during these two ministerial mandates. First of all, the bill, concerning some restrictions on the freedom of the press, which was converted into law on 26 February 1852: the ensuing parliamentary debate led to the fracture of the right and gave rise to the alliance between Rattazzi and Cavour for the formation of a progressive government. Later is illustrated the work carried out by De Foresta in the years 1855-59 for the updating of the codification of the Kingdom of Sardinia through the elaboration of a new code of civil procedure and the revision of the penal codes, which in 1860 replaced the Albertine ones. Finally, is presented the contribution given in 1858 by De Foresta to the alliance with France – deemed indispensable by Cavour to achieve the unity of Italy – when as Minister of Justice, to meet the requests of the French government, pushed through Parliament the laws on sanctions to be imposed on conspirators against foreign heads of state.